Pressure Characteristics Analysis of the Deflector Jet Pilot Stage Under Dynamic Skewed Velocity Distribution - Zhilin Cheng; Wenjun Yang; Liangcai Zeng; Lin Wu (Aerospace, 2025)
The velocity distribution at the deflector jet outlet significantly influences the pressure characteristics of the pilot stage, thereby affecting the dynamic performance of the servo valve. Conventional mathematical models fail to account for the influence of dynamic velocity distribution on pilot stage pressure characteristics, resulting in significant deviations from actual situations. As the deflector shifts, the secondary jet velocity distribution transitions from a symmetric to an asymmetric dynamic profile, altering the pressure within the receiving chambers. To address this, a dynamic skewed velocity distribution model is proposed to more accurately capture the pressure characteristics. The relationship between the skewness coefficient and deflector displacement is established, and the pressure calculation method for the receiving chambers is refined accordingly. A comparative analysis shows that the proposed model aligns most closely with computational fluid dynamics results, achieving a 98% match in velocity distribution and a maximum pressure error of 1.43%. This represents an improvement of 84.98% over the normal model and 82.35% over the uniform model, confirming the superior accuracy of the dynamic skewed model in pilot stage pressure calculation.